Modification, Change, Event: Alain Badiou and Ontology of Historicity - Růžička, Jiří (Dějiny – teorie – kritika, 2016)
This contribution focuses on those parts of Alain Badiou’s ontology and phenomenology which inspire reflection on the nature and the very possibility of historicity as such. Emphasis is on Badiou’s concept of event, its various forms, and consideration of conditions under which events can take place. Analysis of these issues within the context of Marxist tradition of historical materialism is seen as a precondition of re-conceptualisation of philosophy of history in its classical, Kantian and Hegelian guise.